Hepatotoxicity induced by subacute exposure of Mancozeb and Arsenic in Wistar rats: Mitigating effect of quercetin and catechin - Rasia Yousuf; Pawan Kumar Verma; Priyanka Sharma; Shilpa Sood; Nrip K. Pankaj; Zuhaib F. Bhat (Journal of Trace Elements and Minerals, 2024)
Background: Widespread use of Mancozeb (MZ) fungicide in endemic areas having high levels of arsenic (As+3) in the groundwater is likely to cause toxicosis in humans and animals. Therefore, the present study aimed to determine the hepatotoxic effect of MZ and As+3 interaction in Wistar rats and mitigating potential of quercetin and catechin on such toxicity. Methods: Sixty adult rats were randomly divided into 10 groups of 6 animals each. Group I served as control and group II was exposed to MZ (800 mg kg-1, PO). Groups III, IV, and V were provided drinking water containing As+3 at the rate of 10, 50 and 100 µg L-1, respectively. Groups VI, VII, and VIII were given drinking water containing As+3 at 10, 50 and 100 µg L-1, respectively, along with MZ. Groups IX and X received drinking water contaminated with 100 µg L-1, As+3 and MZ along with quercetin or catechin (50 mg kg-1 each), respectively. Results: Significant (p <0.05) alterations in hepatic biomarkers in blood, liver antioxidant status and hepatic histoarchitecture were observed in animals treated with individual toxicants in a dose-dependent manner, however, such toxicity-induced changes were more severe in co-exposed rats. The administration of quercetin or catechin significantly mitigated the dual toxicant administration-driven changes in biochemical markers of hepatic damage, hepatic antioxidant profile and liver histomorphology. Conclusions: Both quercetin and catechin proved beneficial in reducing toxicant-induced oxidation-mediated hepatic damage as demonstrated by alleviation in altered levels of determinants of hepatic biochemical and oxidative stress parameters in addition to restoration of toxicant-induced histological alterations of hepatic tissue.